(untitled) (Studia theodisca, 2011)
Edith Kneifl’s thrillers follow a double geographical dimension, since Italy and Austria form the narrative setting of her criminal minds. Women who recall Lucrezia Borgia and men under the impulse of uncontrolled violent emotions move from town to town showing that the criminal setting is not just a plain narrative landscape but rather more of a topographic and topologic stage on which the human identity can let its unconsciousness be free to self-determination.